The overlooked role of biotic factors in controlling the ecological performance of artificial marine habitats. Issue 1 (3rd October 2015) - Ferrario, Filippo; Iveša, Ljiljana; Jaklin, Andrej; Perkol‐Finkel, Shimrit; Airoldi, Laura
Summary: Artificial structures are sprawling in marine seascapes as a result of burgeoning coastal populations, increasing development and energy demand, and greater risks from climate change, storm surges and sea level rise. Interest in designing marine developments that maintain vital ecosystems and critical services is growing, but progress requires understanding the factors that influence the ecological performance of these novel artificial habitats. We combined field observations and experiments along 500 km of the North Adriatic coastline to analyse the performance of artificial substrata as habitats to support canopy‐forming algae belonging to the genus Cystoseira, among the most ecologically relevant foundation species along rocky Mediterranean coastlines. We aimed to: clarify the underlying factors controlling the growth of Cystoseira in the artificial habitat; contrast the relative importance of these factors between artificial and natural habitats; and test the generality of the results across different sites and species of Cystoseira . We found that: (i) the growth of canopy algae was significantly lower on artificial structures compared to rocky reefs; (ii) such lower growth of canopy algae was not related to less favourable abiotic conditions but to higher biotic disturbance from both consumptive and nonconsumptive interactions on the artificial structures compared to the natural reef; and iii) this was consistent across different study sites and canopy‐forming species. We conclude that biological factors influencing the growth of canopy algae, such as herbivory or other nonconsumptive disturbances, can differ substantially between artificial and natural habitats. The unusually large and previously unreported biotic pressure characterizing many artificial structures can negatively affect their performance as habitats to support ecologically relevant, foundation species. Synthesis and applications . While nearly all considerations to improve the ecological performance of hard marine infrastructures focus on abiotic factors (e.g. construction materials, surface texture, habitat complexity or water quality), careful consideration of critical biotic factors is also needed to further progress the green engineering of sprawling marine infrastructures.